2012
DOI: 10.1016/j.bbmt.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-Dose versus Low-Dose Cyclophosphamide and Granulocyte Colony-Stimulating Factor for Peripheral Blood Stem Cell Mobilization in Patients with Multiple Myeloma Treated with Novel Induction Therapies

Abstract: Peripheral blood progenitor cell mobilization with intermediate-dose cyclophosphamide (ID-CY) and granulocyte colony-stimulating factor (G-CSF) has been shown to be more efficacious, albeit more toxic, than low-dose cyclophosphamide (LD-CY) mobilization regimens in patients with multiple myeloma treated with conventional therapies. However, the relative importance of cyclophosphamide dose intensity in peripheral blood progenitor cell mobilization after novel induction regimens is not known. Here we report mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 23 publications
2
45
0
7
Order By: Relevance
“…Retrospective studies comparing different CY doses have shown a higher CD34+ cell yield associated with higher dose of CY but with more considerable toxicity, which limits the use of very high dose CY (7 g/m 2 ) and favor the use of intermediate-to-high dose. 6,8,9 Indeed, fractionation of CY in our study allowed administration of a relatively high dose of CY (5 g/m 2 ) with decreased immediate toxicity, mainly nausea and vomiting, but was still associated with significant hematological toxicity.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Retrospective studies comparing different CY doses have shown a higher CD34+ cell yield associated with higher dose of CY but with more considerable toxicity, which limits the use of very high dose CY (7 g/m 2 ) and favor the use of intermediate-to-high dose. 6,8,9 Indeed, fractionation of CY in our study allowed administration of a relatively high dose of CY (5 g/m 2 ) with decreased immediate toxicity, mainly nausea and vomiting, but was still associated with significant hematological toxicity.…”
Section: Discussionmentioning
confidence: 81%
“…Median time to neutrophil engraftment was 11 days (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in the CY group compared with 12 days (10-15) in the plerixafor group (P = 0.027). Similarly, median time to platelet engraftment was 12 days (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) in the CY group compared with 12 days (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in the plerixafor group (P = 0.12).…”
Section: Mobilization Efficiencymentioning
confidence: 93%
See 1 more Smart Citation
“…The standard regimen for stem cell mobilization in younger patients with MM consists of CY followed by granulocyte colony-stimulating factor (G-CSF) administration. Compared to the intermediate dose of CY at 3-4 g/m 2 , a dose reduction to CY to 1.5 g/m 2 may reduce the incidence of febrile neutropenia, although the yield of CD34+ cells harvested would be lower (23). In the current study, 10 elderly patients (one patient older than 70 years) received 4 g/m 2 of CY for stem cell mobilization, while eight elderly patients (five patients older than 70 years) received a decreased dose of CY of 2-3 g/m 2 ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…(12,40) Mobilisation chemotherapy and stem cell collection High-dose cyclophosphamide (Cy) at 4-7 g/m 2 with granulocyte colony-stimulating factor (GCSF) has been shown to be effective for haematopoietic progenitor cell mobilisation despite associated haematologic toxicity. (59) Vinorelbine 25 mg/m 2 in combination with Cy 1,500 mg/m 2 (Vino-Cy) was shown to be comparable to Cy mobilisation in a study using historical controls. (12,60) We recommend one of the following mobilisation protocols: A haematopoietic progenitor cell collection adequate for two SCTs should be the target; this is conventionally accepted to be greater than 5 × 10 6 per kg/body weight.…”
Section: Choice Of Induction Therapymentioning
confidence: 99%